(untitled)
Price discrimination by consumer's purchase history is widely used in regulated industries, such as communication or utilities, both by incumbents and entrants. I show that such discrimination can have surprisingly negative welfare effects even though prices and industry profits fall, so does consumer surplus. Earlier studies that did not allow entrants to discriminate or assumed symmetric firms yielded sharply different results, the procompetitive effect of price discrimination are stronger in these settings. Imposing a pricing constraint on incumbent's discrimination leads the entrant to discriminate more heavily, but still improves both consumer and producer welfare., address = Milano, author = Hinnerk Gnutzmann, copyright = http://www.econstor.eu/dspace/Nutzungsbedingungen, keywords = L13; L41; 330; Historybased price discrimination; asymmetric price discrimination; switching cost, language = eng, number = 19, publisher = Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), title = Price Discrimination in Asymmetric Industries: Implications for Competition and Welfare, type = Working Paper, url = https://hdl.handle.net/10419/170616, year = 2014